The effect of novel biotechnological vermicompost on tea yield, plant nutrient content, antioxidants, amino acids, and organic acids as an alternative to chemical fertilizers for sustainability - Kocaman, Ayhan; Inci, Yusra; Kitir, Nurgul; Turan, Metin; Argin, Sanem; Yildirim, Ertan; Giray, Gulay (Bmc, 2024)
In this study, the performance of a novel organic tea compost developed for the first time in the world from raw tea waste from tea processing factories and enriched with worms, beneficial microorganisms, and enzymes was tested in comparison to chemical fertilizers in tea plantations in Rize and Artvin provinces, where the most intensive tea cultivation is carried out in Turkey. In the field trials, the developed organic tea vermicompost was incorporated into the root zones of the plants in the tea plantations in amounts of 1000 (OVT1), 2000 (OVT2) and 4000 (OVT4) (kg ha(-1)). The experimental design included a control group without OVT applications and positive controls with chemical fertilizers (N: P: K 25:5:10, (CF) 1200 kg ha(-1)) commonly used by local growers. The evaluation included field trials over two years. The average yields obtained in two-year field trials in five different areas were: Control (6326), OVT1 (7082), OVT2 (7408), OVT4 (7910), and CF (8028) kg ha(-1). Notably, there was no significant statistical difference in yields between the organic (at 4000 kg ha(-1) ) and chemical fertilizers (at 1200 kg ha(-1)). The highest nutrient contents were obtained when CF and OVT4 were applied. According to the average values across all regions, the application of OVT4 increased the uptake of 63% N, 18% K, 75% P, 21% Mg, 19% Na, 29% Ca, 28% Zn, 11% Cu and 24% Mn compared to the control group. The application of chemical fertilizers increased the uptake of 75% N, 21% K, 75% P, 21% Mg, 28% Na, 27% Ca, 30% Zn, 18% Cu and 31% Mn compared to the control group. The organic fertilizer treatment had the lowest levels of antioxidants compared to the control groups and the chemical fertilizers. It was also found that the organic fertilizer increased the levels of amino acids, organic acids and chlorophyll in the tea plant. Its low antioxidant activity and proline content prepared them for or protected them from stress conditions. With these properties, the biotechnologically developed organic tea compost fertilizer has proven to be very promising for tea cultivation and organic plant production.
Keywords: Tea waste; Biotechnology; Organic fertilizer; Tea cultivation; Yield; Amino acids